Epidemiology of atopic dermatitis in adults: Results from an international survey. Issue 6 (13th February 2018) - Barbarot, S.; Auziere, S.; Gadkari, A.; Girolomoni, G.; Puig, L.; Simpson, E. L.; Margolis, D. J.; de Bruin‐Weller, M.; Eckert, L.
Abstract: Background: There are gaps in our knowledge of the prevalence of adult atopic dermatitis (AD). Objective: To estimate the prevalence of AD in adults and by disease severity. Methods: This international, cross‐sectional, web‐based survey was performed in the United States, Canada, France, Germany, Italy, Spain, United Kingdom, and Japan. Adult members of online respondent panels were sent a questionnaire for AD identification and severity assessment; demographic quotas ensured population representativeness for each country. A diagnosis of AD required subjects to be positive on the modified UK Working Party/ISAAC criteria and self‐report of ever having an AD diagnosis by a physician. The proportion of subjects with AD who reported being treated for their condition was determined and also used to estimate prevalence. Severity scales were Patient‐Oriented SCORAD, Patient‐Orientated Eczema Measure, and Patient Global Assessment. Results: Among participants by region, the point prevalence of adult AD in the overall/treated populations was 4.9%/3.9% in the US, 3.5%/2.6% in Canada, 4.4%/3.5% in the EU, and 2.1%/1.5% in Japan. The prevalence was generally lower for males vs females, and decreased with age. Regional variability was observed within countries. Severity varied by scale and region; however, regardless of the scale or region, proportion of subjects reporting severe disease was lower than mild or moderate disease. Conclusions: Prevalence of adult AD ranged from 2.1% to 4.9% across countries. Severe AD represented a small proportion of the overall AD population regardless of measure or region.